Tingkat Kegunaan Sarana Pendukung Aksesibilitas Jamaah Difabel Bangunan Masjid Jami At Taqwa Perumahan Minomartani Sleman - Dhea Nisa Miftahul Jannah; Sri Ngesti Mumpuni; Karto Wijaya; Fatin Nursyaza (Fakultas Teknik - Universitas Bung Karno, 2024)
The existence of the Jami Al Taqwa Minomartani mosque is a public building which is a place of worship as well as various other activities related to the mental, cultural and social development of the Islamic community living in the Minomartani housing area. In accordance with government regulations regarding accessibility requirements, including for disabled worshipers, the building's supporting facilities must support these conditions. This research aims to find out how much facilities exist that support this accessibility in order to provide constructive input that is beneficial for the mosque's prosperity program. The method used is observation and analysis of existing data, then interpretation is carried out using the criteria for accessibility requirements. Research findings show that this mosque can be categorized as a mosque that is aware of its congregation with disabilities by providing facilities to support this accessibility. However, regarding the level of usability, it still needs to be improved in relation to the requirements so that it has an optimal level of effectiveness.